TRP Channels in Brain Tumors - Chinigò, Giorgia; Castel, Hélène; Chever, Oana; Gkika, Dimitra (Frontiers in Cell and Developmental Biology, 2021)
Malignant glioma including glioblastoma (GBM) is the most common group of primary brain tumors. Despite standard optimized treatment consisting of extensive resection followed by radiotherapy/concomitant and adjuvant therapy, GBM remains one of the most aggressive human cancers. GBM is a typical example of intra-heterogeneity modeled by different micro-environmental situations, one of the main causes of resistance to conventional treatments. The resistance to treatment is associated with angiogenesis, hypoxic and necrotic tumor areas while heterogeneity would accumulate during glioma cell invasion, supporting recurrence. These complex mechanisms require a focus on potential new molecular actors to consider new treatment options for gliomas. Among emerging and underexplored targets, TRP (Transient Receptor Potential) channels belonging to a superfamily of non-selective cation channels which play critical roles in the responses to a number of external stimuli from the external environment were found to be related to cancer development, including glioma. Here we discuss the potential diagnosis and prognosis biological marker potentially played by TRPC6, TRPM8, TRPV4 or TRPV1/V2 being associated with glioma patient overall survival. TRPs-inducing common or distinct mechanisms associated with their Ca2+-channel permeability and/or kinase function were detailed as involving miRNA or secondary effector signaling cascades in turn controlling proliferation, cell cycle, apoptotic pathways, DNA repair, resistance to treatment as well as migration/invasion. These recent observations of the key role played by TRPs as TRPC6 in GBM growth and invasiveness, TRPV2 in proliferation and glioma-stem cell differentiation and TRPM2 as channel carriers of cytotoxic chemotherapy within glioma cells, should offer new directions for innovation in treatment strategies of high-grade glioma as GBM to overcome high resistance and recurrence.